Gaillardin, a potent sesquiterpene lactone induces apoptosis via down-regulation of NF‐κβ in gastric cancer cells, AGS and MKN45. (5th December 2021) - Roozbehani, Maryam; Abdolmohammadi, Mohammad Hossein; Hamzeloo-Moghadam, Maryam; Irani, Shiva; Fallahian, Faranak
Abstract: Ethnopharmacological relevance: The genus Inula has been traditionally used as folk medicine in treating different illnesses such as kidney stones, urethra infection, jaundice, bronchitis, respiratory diseases and cancer. Aim of the study: Gaillardin, a sesquiterpene lactone isolated from Inula oculus-christi, seems to have great potential as an anti-cancer agent. This study was carried out to evaluate the anti-cancer properties of Gaillardin in gastric cancer cells and also its possible underlying mechanism. Methods: The colorimetric MTT assay was used to assess metabolic activity of cells as an indicator of viability and cytotoxicity. Flow cytometry using Annexin V-FITC/PI was applied to detect and quantify the level of apoptosis. Detection of activated caspase-3, as a biochemical marker of apoptosis, was done using caspase-3 assay kit. Activation of NF-κB pathway was determined by western blotting. The mRNA expression levels of NF-κB target genes were measured using quantitative RT-PCR. Moreover, intracellular reactive oxygen species (ROS) production was evaluated. Results: Gaillardin significantly reduced cell viability in a time and dose-dependent manner. The inhibitory effect of Gaillardin was attributed to induction of apoptosis. Investigation about the underlying mechanism revealed that Gaillardin exerts its action through inhibition of NF-κB activation and subsequently down-regulation of genes (COX-2, MMP-9, TWIST-1, and BCl-2) regulated by NF-κB. Moreover, Gaillardin caused remarkable elevation in ROS production in AGS and MKN45 cells. Conclusion: We provided evidences about the role of NF-κB pathway in the induction of apoptosis by the sesquiterpene lactone Gaillardin in AGS and MKN45 cells for the first time, which suggest Gaillardin could be considered as a promising natural agent for further investigations to identify new potent anticancer drugs in the future. Graphical abstract: Image 1 Highlights: Gaillardin induced cell growth inhibition in AGS and MKN45 cells. Apoptotic cell death was involved in Gaillardin-mediated cytotoxicity. Apoptotic effects of Gaillardin might be attributed to inhibition of NF-κB pathway. Down-regulation of COX-2, MMP-9, TWIST-1, BCl-2, and up-regulation of Bax were detected in treated cells with Gaillardin. ROS level was remarkably increased in response to Gaillardin.